Mengurai Persepsi Publik Terkait Aerostreet: Analisis Media Monitoring pada Bulan Februari 2024 - Simamora, Moni Berliani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Aerostreet is one of the local shoe brands that is popular among the public in Indonesia. With the high popularity of Aerostreet today, it is important to conduct media monitoring to find out and track issues or information related to the company on various media platforms. This study aims to analyze the results of media monitoring of Aerostreet in the period 1–29 February 2024 using the quantitative descriptive method. Data collection was conducted online using media monitoring tools such as Brand24. The data obtained through Brand24 includes websites, news, forums, videos, blogs, Twitter, and Tiktok. The results of this study show that the mentions and reach of Aerostreet are 361 and 1,284,781, respectively. The number of positive sentiments about Aerostreet is 96, or 74%. The number of news related to Aerostreet is 52, with a very fluctuating increase every week. The most discussed news topics by the media related to Aerostreet are about Gibran and Aerostreet's collaboration in supporting the local shoe industry, quality local shoe recommendations, and also off-air events of Aerostreet's collaboration with Tokopedia in launching Looney Tunes T-shirt products.